Post a New Question

math

posted by on .

Solve the equation
3^2x - 12 x 3^x + 27 = 0

  • math - ,

    let 3^x = y
    so we get

    y^2 - 12y + 27 = 0
    (y-3)(y-9) = 0
    y = 3 or y = 9
    then
    x^2 = 3 or x^2 = 9
    x = ± √3 or x = ± 3

    btw, in something like 12 x 3^x , do not use x as a multiplication sign, especially if you have a variable x
    either say just 12(3^x) or say 12*3^x

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question